Improving The Writing Skills of Vocational High School in Payakumbuh Teachers Through a Blog-Based Autobiographical Technique Workshop - Lani, Oktri Permata; Mastanora, Refika; Silvira, Melva; Kholijah, Siti (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2024)
Improving skills should be a concern for educators to support student abilities, but not all educators pay attention to the importance of improving skills. One of them is in terms of writing for teachers at the Vocational High School level. At Vocational High School in Payakumbuh, which is a Vocational School that has majors including Computer Network Engineering, Multimedia, and Software Engineering (Broadcasting), with the sophistication of this IT-based school, of course, it already has facilities in the field of Information and Communication Technology that are qualified. The type of research used is in the form of School Action Research (PTS). School Action Research is an amalgamation of action research. Action research was developed with the intention of finding solutions to social problems. Action research begins with a systematic study of a problem. The results of the study are used as the basis for developing a work plan (action) in an effort to overcome the problem. The conclusion obtained from the research on improving the writing ability of Vocational High School in Payakumbuh teachers through blog-based autobiographical techniques is that there is an increase in the writing ability of Vocational High School in Payakumbuh teachers after attending a workshop on blog-based autobiographical techniques. Teachers' motivation to improve their writing skills also increased, and enthusiasm for using blog or website media to be more optimized.